PSYCHOMETRIC ANALYSIS OF SELF-COMPASSION SCALE FOR ADOLESCENTS - Koko, Abdullah Korano Prajab; Setiawati, Farida Agus; Saifuddiin, Muhammad Rizqi (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study aims to develop a psychological measurement tool on self-compassion for adolescents. The sample consisted of adolescents aged 17 to 20 years, 97 participants (64 female, 33 male), the sample was randomly selected. Psychometric analysis involved content validity, item fit analysis, CFA, and reliability of the measure. Reliability results from psychometric analysis showed good internal results, from the results of CFA calculations showed that this scale has a fit model so it can be concluded that this adolescent self-compassion measurement tool can be used as a qualified scale to measure adolescent self-compassion.